Ứng dụng chatbot trong hướng dẫn kĩ năng xã hội cho thanh thiếu niên rối loạn phổ tự kỉ trong hoạt động hướng nghiệp: Một nghiên cứu tại Thành phố Hà Nội - Đào Thị Thu, Thủy; Nguyễn Thị , Huyền; Nguyễn Thị Quỳnh , Hoa (Tạp chí Giáo dục, 2026)
This study examines the application of Chatbot technology in social skills instruction for adolescents with autism spectrum disorder participating in career guidance activities at S.E.E.D Center, Hanoi. Using a mixed-methods approach that combined literature review and field-based data collection, the study investigated the current status of social skills, challenges encountered in instruction, and the potential role of Chatbot in career-oriented educational settings. The findings revealed a clear distinction between routine social skills and functional social skills associated with vocational contexts, with the latter remaining a major area of difficulty for adolescents with autism spectrum disorder. The results also indicated that teachers held positive perceptions regarding the applicability of Chatbot in supporting social skills practice through structured, safe, and repeatable interactions. Based on these findings, the study proposes several recommendations, including the development of appropriate interaction scenarios, the integration of Chatbot into instructional processes, and professional development for teachers to support social skills development in career guidance programs for adolescents with autism spectrum disorder.